2013
DOI: 10.1159/000350067
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bone Mineral Density with Albuminuria and Estimated Glomerular Filtration Rate : The Dong-gu Study

Abstract: Background: Kidney dysfunction and albuminuria may be associated with BMD. However, little evidence has been reported on relationships between BMD and eGFR and albuminuria. Methods: A total of 8,992 subjects aged 50 years or older participated in a survey conducted. Participants had their lumbar spine and femoral neck BMD measured by a Lunar Prodigy bone densitometer (GE, Madison, WI). Kidney function was assessed using MDRD eGFR and diagnosis of albuminuria was based on albumin-creatinine ratio. Results: ACR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
1
13
1
Order By: Relevance
“…In trying to elucidate the implications of kidney function on BMD in elderly women, we began by performing a non-systematic literature search. Although lack of longitudinal studies and differences in study populations make comparison of results difficult, this search indicated an association between kidney function and BMD [ 17 21 , 23 , 28 , 30 ], though whether mediated through differences in sex, age and weight is unclear [ 18 , 19 ]. The homogeneity of the OPRA cohort, followed for 10 years, allowed us to address this gap in knowledge and make reliable conclusions about the association between kidney function and BMD in this elderly age group.…”
Section: Discussionmentioning
confidence: 99%
“…In trying to elucidate the implications of kidney function on BMD in elderly women, we began by performing a non-systematic literature search. Although lack of longitudinal studies and differences in study populations make comparison of results difficult, this search indicated an association between kidney function and BMD [ 17 21 , 23 , 28 , 30 ], though whether mediated through differences in sex, age and weight is unclear [ 18 , 19 ]. The homogeneity of the OPRA cohort, followed for 10 years, allowed us to address this gap in knowledge and make reliable conclusions about the association between kidney function and BMD in this elderly age group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many previous laboratory studies have suggested that angiogenesis promoted osteogenesis. 2,3 Choi et al 4 reported that the urine albumin-creatinine ratio (ACR) was negatively correlated with bone mineral density (BMD) at the lumbar spine and femoral neck in females. Another survey 5 with follow-up lasing 8.4 years from Norway demonstrated that ACR was associated with non-vertebral fractures in females without diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…A few large cross‐sectional studies have reported that increased urine albumin is associated with lower BMD, but prospective analyses appear inconclusive and limited to small studies in narrow populations . Prospective studies have reported a positive association between urine albumin and risk of nonvertebral fractures, with some, but not all, reporting that the increased risk was present only in women and not men.…”
Section: Introductionmentioning
confidence: 99%